PARTICIPATORY MARKETING COMMUNICATION: IMPROVE THE IMAGE OF TOURISM DESTINATIONS IN NORTH LOMBOK - Sutama, I Wayan; Pawito, Pawito; Hastjarjo, Sri; Demartoto, Argyo (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
As a tourist destination, North Lombok possesses substantial natural and cultural potential; however, the challenges in constructing the destination's image are primarily associated with the digital literacy of the local populace. This article examines the efficacy of participatory marketing communication in integrating the image of tourism destinations in North Lombok through community empowerment and community-based digital strategies. Utilizing a case study approach, this research investigates the effectiveness of community-based marketing in reinforcing destination branding. The study's findings indicate that the community's active engagement in promoting tourism plays a crucial role in shaping destination branding, wherein destinations that combine natural and cultural elements exhibit significant potential for development as sustainable tourism assets. Furthermore, the suboptimal synergy among government entities, the community, and tourism industry stakeholders represents a considerable impediment to achieving integrated and sustainable destination promotion. The wisdom of Wetu Telu serves as a foundation for fostering social harmony amidst diversity and multiculturalism, maintaining social stability, and encouraging the development of a tolerant society prepared to accommodate diverse tourist backgrounds in inclusive and sustainable tourism development.